PENGARUH KARAKTERISTIK DEWAN KOMISARIS DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA BERBASIS AKTIVITAS REAL - Melissa Devina Nugroho; Sansaloni Butar-Butar (Universitas Katolik Soegijapranata Semarang, 2013)
This paper examines the effect of board characteristics and institutional ownership on real earnings management. Previous studies have shown that boards monotoring functions increasing as the ouside members increased and tended to decrease when they also serve as board commissioner in another company. Therefore, board commissioners independence are predicted to negatively effect real earnings managements, and the number of jobs that independent members takes in another company positively effect real earnings management. Meanwhile, the institutional ownership is predicted to reduce real earnings management. Firms samples are from Indonesia Stock Exchange in the period 2007-2010. Hypothesis testing is performed by multiple linear regression. The result findings are summarized as follows: 1) independence of the board of commissioners is inversely related to real earnings management, 2) firms having independent members who are also a member of board of commissioners in another company have higher real earnings management than firms with independent board that had not served same position in other companies, 3) institutional ownership negatively effect real earnings management, 4) managerial ownership negatively effect real earnings management.